A revision of subspecies structure of western honey bee Apis mellifera - Ilyasov, Rustem A.; Lee, Myeong-lyeol; Takahashi, Jun-ichi; Kwon, Hyung Wook; Nikolenko, Alexey G. (Saudi Journal of Biological Sciences, 2020)
The taxonomy of honey bee A. mellifera contains a lot of issues due to the specificity of population structure, features of biology and resolutions of honey bee subspecies discrimination methods. There are a lot of transition zones between ranges of subspecies which led to the gradual changes of characteristics among neighbor subspecies. The modern taxonomic pattern of honey bee Apis mellifera is given in this paper. Thirty-three distinct honey bee subspecies are distributed across all Africa (11 subspecies), Western Asia and the Middle East (9 subspecies), and Europe (13 subspecies). All honey bee subspecies are subdivided into 5 evolutionary lineages: lineage A (10 subspecies) and its sublineage Z (3 subspecies), lineage M (3 subspecies), lineage C (10 subspecies), lineage O (3 subspecies), lineage Y (1 subspecies), lineage C or O (3 subspecies).